2009
DOI: 10.1080/10715760902902737
|View full text |Cite
|
Sign up to set email alerts
|

F2-Isoprostanes, tocopherols and normal pregnancy

Abstract: This study investigates oxidative stress and antioxidants in normal human pregnancy and post-partum period. Thirty-seven healthy women with normal pregnancies were included. Both urinary and serum samples were collected throughout the pregnancy and post-partum period. Oxidative stress was estimated by measuring the reliable in vivo marker, namely 8-iso-prostaglandin F(2alpha) (8-iso-PGF(2alpha,) an F(2)-isoprostane) and antioxidant status was evaluated by measuring alpha- and gamma-tocopherol in serum samples.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 27 publications
2
25
0
1
Order By: Relevance
“…It anchors the conceptus, provides an interface for the exchange and modification of nutrients and gases, synthesizes and secretes a range of steroid and peptide hormones, and provided an immune barrier between the mother and the semi-allogeneic fetus. 27 Measurements of oxidative stress markers in maternal blood and urine 28 show that pregnancy per se is a state of oxidative stress due to the high metabolic activity of the placenta and maternal metabolism in pregnancy. 27 Our results showed that mild diabetes caused no change in the SOD activity and MDA concentration in the placental tissue samples, however, the catalase activity was increased.…”
Section: Discussionmentioning
confidence: 99%
“…It anchors the conceptus, provides an interface for the exchange and modification of nutrients and gases, synthesizes and secretes a range of steroid and peptide hormones, and provided an immune barrier between the mother and the semi-allogeneic fetus. 27 Measurements of oxidative stress markers in maternal blood and urine 28 show that pregnancy per se is a state of oxidative stress due to the high metabolic activity of the placenta and maternal metabolism in pregnancy. 27 Our results showed that mild diabetes caused no change in the SOD activity and MDA concentration in the placental tissue samples, however, the catalase activity was increased.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that oxidative and nitrative stress can lead to altered placental function via covalent modification of protein structure and function. Measurements of markers of oxidative stress in maternal blood and urine [1315] show that pregnancy per se is a state of oxidative stress due to the high metabolic activity of the placenta and maternal metabolism in pregnancy. However, this is heightened in pregnancies complicated by preeclampsia, IUGR and diabetes as measured by increased markers of production of reactive oxygen species and decreases in antioxidant defences [11, 1618].…”
Section: Generation Of Oxidative and Nitrative Stress In The Placentamentioning
confidence: 99%
“…Pregnancy, with a moderate state of systemic inflammation 4 and a state of increase oxidative stress, 5 is related to a higher production of reactive oxygen species (ROS) 6 . It has been proposed that an imbalance between the synthesis of nitric oxide and ROS produces endothelial dysfunction 7 .…”
Section: Introductionmentioning
confidence: 99%